Madame de Staël and the women alchemists of happiness - Ruiz Callejón, Encarnación (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper analyses Madame de Staël’s reflections on happiness, why she believes that we start from an erroneous conception, why passions are a decisive factor and what resources we have at our disposal to be happy. With regard to the latter, this paper analyses why the protagonists of her two great novels, Delphine and Corinne, fail, what the position of the male characters is and whether the author offers women other means of pursuing happiness.